Conceptualization of the Cultural and Artistic Model of the Ecological Competence of the Mathematics Teacher - Klochko, Oksana; Fedorets, Vasyl (Educological discourse, 2023)
The article represents the concept of the cultural and artistic model of the ecological competence of the mathematics teacher. The work used a system of methods and approaches, among which innovative, ecological, competence, systemic, anthropological, cultural, axiological, aesthetic, artistic, epistemological were the defining ones. The developed "Cultural-artistic model of ecological competence of a mathematics teacher" contains 4 components - cognitive, activity, personal-psychological and cultural-artistic. The ecological competence of the mathematics teacher has a functional focus on integrative ecologization, aestheticization, axiologization, and ethicization of the cultural and educational space and on the development of a harmonious and healthy personality. In the components of ecological competence, the mathematical dimension is significant. In the cognitive component, this is mathematical knowledge, ideas, and cognitive skills and schemes through which the phenomenology of ecological problems is revealed. In the cultural and artistic component, mathematics is used to reveal the phenomenology of the aesthetic, artistic, harmonious, perfect. In the personal and psychological component, the ideas of harmony are actualized. The activity component is aimed at the integrative disclosure of mathematical, ecological, artistic, ethical and aesthetic phenomena. The directions of ecologization, mathematization, aestheticization, ethicization, axiologisation, and psychologization of the cultural and educational space are integrated into the system of ecological competence of the mathematics teacher. During the formation and implementation of ecological competence, methodical disciplines were developed and applied. The specified methodological disciplines are purposefully formed for the integration and target (ecological, mathematical and aesthetic) and competence orientation of knowledge, values, meanings, ethical attitudes, prescribed from various subject areas. Accordingly, propaedeutic and therapeutic poles formed by methodical disciplines are distinguished in ecological competence.